The role of metal element exposure and oxidative stress in mild cognitive impairment: Evidence from a Shanghai elderly cohort - Ying Qing; Jianheng Zheng; TianRan Tang; Yingyi Luo; Dan Han; Liqiang Wang; Yaxin Dong; Shuyu Yang; Jun Du; Yanfei Li (Ecotoxicology and Environmental Safety)
This study, based on a cross-sectional study of elderly individuals in Shanghai, explored the associations between mixed metal element exposure and mild cognitive impairment (MCI), as well as the mediating role of oxidative stress. We assessed MCI using the Montreal Cognitive Assessment (MoCA) scale and measured plasma levels of amyloid β40 (Aβ40), Aβ42, Aβ42/40, total tau (T-tau) and phosphorylated tau (P-tau) proteins. Spearman’s correlation analysis, linear regression, weighted quantile sum (WQS) regression, and quantile g-computation (qgcomp) modeling were used to assess the associations between metal elements and MCI, and to analyze the mediating role of oxidative stress using mediation models. The results showed significant differences in blood cadmium (Cd), lead (Pb), copper (Cu), zinc (Zn), and selenium (Se) levels between the MCI group and the normal cognition group. MoCA scores were negatively correlated with Cd, Pb, and Cu levels, and positively correlated with Zn and Se levels. Aβ42 and Aβ42/40 were negatively correlated with Cu and positively correlated with Zn and Se. P-tau was positively correlated with mercury (Hg). The WQS index was significantly negatively correlated with the MoCA score, with Cu contributing the most (84.0 %). Meanwhile, Aβ42 and Aβ42/40 were significantly positively correlated with the WQS index, with Se (34.0 %) and Zn (58.3 %) being the main contributors. Qgcomp modeling also found that mixed exposure to metal elements was significantly negatively correlated with the MoCA score, with Cu given the highest negative weight (-0.601). SOD partially mediated the correlation of Cu, Zn, Se, and WQS index with Aβ42 (mediation ratio of 14.3–27.8 %). This study provides population-based evidence for identifying factors and potential mechanisms affecting MCI.